Social Policy Implications: Comparative Analysis of Diabetes Mellitus Coding Accuracy in Public and Private Hospitals: Implikasi Kebijakan Sosial: Analisis Perbandingan Akurasi Kode Diabetes Mellitus di Rumah Sakit Swasta dan Pemerintah - Prayuda, Muhammad Galih; Nisak, Umi Khoirun (Universitas Muhammadiyah Sidoarjo, 2023)
This study investigates the critical role of coding accuracy in managing medical records, focusing on data completeness in healthcare services. Utilizing 30 medical records from two distinct hospitals, the research evaluates the completeness of diagnostic information. Results reveal significant differences between Hospital Bhayangkara Pusdik Porong, with 46.7% complete records, and Hospital 'Aisyiyah Siti Fatimah Tulangan, presenting 73.3% completeness. The Non-Parametric Independent-Samples Mann-Whitney Test yields a significant value of p=0.037, indicating a noteworthy disparity between the two institutions. These findings emphasize the necessity of standardized coding practices to enhance data accuracy and consistency in healthcare, highlighting implications for improved record-keeping and information management strategies. Highlights: Coding Accuracy: Highlighting the crucial role of precise coding in healthcare data management. Institutional Disparities: Signifying notable differences in data completeness between distinct hospitals. Standardization Need: Emphasizing the necessity for standardized coding practices to ensure consistent and accurate healthcare records. Keywords: Healthcare, Data Coding, Medical Records, Completeness, Comparative Analysis